Cd diminution through microbial mediated degraded lignocellulose maize straw: Batch adsorption and bioavailability trails. (15th January 2022) - Haris, Muhammad; Hamid, Yasir; Wang, Lei; Wang, Min; Yashir, Nauman; Su, Fang; Saleem, Atif; Guo, JunKang; Li, Yongtao
Abstract: Lignocellulose degraded maize straw (LMS) was prepared with the interaction of soil-indigenous microorganisms and further deployed to attenuate the Cd contamination in polluted soil. The Lignocellulose degrading ratio was determined and results revealed the significant degradation of cellulose, hemicellulose and lignin by 33.03, 26.7 and 15.97% respectively as compared to pristine maize straw (PS). Moreover, LMS was also categorized through FE-SEM, FTIR, BET analysis, elemental analysis and XPS technique and the analytical results indicated that lignocellulose structure in maize straw was successfully degraded and was involved in metal-ion complexation. Batch sorption trials revealed that Cd 2+ sorption onto LMS was explained well by Langmuir isotherm and pseudo-second-order kinetic model. The LMS showed maximum adsorption capacities (9.84 mg g −1 ) for Cd 2+ as compared to PS (3.30 mg g −1 ). Moreover, the soil incubation trials (60 days) depicted the availability of Cd decreased by 11.03 and 34.7% with PS and LMS application respectively. The addition of LMS significantly decreased the exchangeable fractions of Cd and ensued an increase in organic matter and Fe–Mn oxides bound fractions. This work clarified the LMS as a promising amendment for effective remediation of Cd-contaminated matrices. Graphical abstract: Image 1 Highlights: Efficacy of pristine and degraded straw was evaluated via batch sorption and incubation trials. The degraded straw showed high adsorption capacity (9.84 mg g −1 ) than pristine straw (3.30 mg g −1 ). Lignocellulose degraded straw established more binding sites owing to functional moieties. The Cd availability reduced by 34.7% with amending of degraded straw than pristine straw 11.03%.